2012
DOI: 10.1212/wnl.0b013e3182735cd7
|View full text |Cite
|
Sign up to set email alerts
|

Generalized periodic discharges in the critically ill

Abstract: Objective: Generalized periodic discharges are increasingly recognized on continuous EEG monitoring, but their relationship to seizures and prognosis remains unclear.Methods: All adults with generalized periodic discharges from 1996 to 2006 were matched 1:1 to controls by age, etiology, and level of consciousness. Overall, 200 patients with generalized periodic discharges were matched to 200 controls. Results:Mean age was 66 years (range 18-96); 56% were comatose. Presenting illnesses included acute brain inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
162
1
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(193 citation statements)
references
References 31 publications
13
162
1
6
Order By: Relevance
“…In a study of 200 patients with GPED, it was ascertained that the most common etiologies found through cEEG monitoring were toxic-metabolic encephalopathy, septicemia, and stroke and that GPED was associated with the high incidence of NCS-NCSE (20). Similar to this study, the presence of NCS-NCSE showed significantly high association with GPED in our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a study of 200 patients with GPED, it was ascertained that the most common etiologies found through cEEG monitoring were toxic-metabolic encephalopathy, septicemia, and stroke and that GPED was associated with the high incidence of NCS-NCSE (20). Similar to this study, the presence of NCS-NCSE showed significantly high association with GPED in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies suggested that the use of wave morphology and/or response to intravenous benzodiazepine could help in diagnosis (20). In our study, the presence of metabolic disorder (specifically electrolyte disturbance) was significantly high in the patients with GPED having TW morphology.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The normal EEG, atypical PSWC or other EEG findings were converted to typical PSWC in most cases. The difference between the two drugs was not statistically significantly different [11]. In fact, for the respiratory side effects, midazolam is preferred to diazepam in certain conditions [7].…”
Section: Discussionmentioning
confidence: 78%
“…Although we had good enough samples in the particular time, larger samples could make the results different. One study administered both the drugs in same person in consecutive days [11]. It would be better if we could do so.…”
Section: Discussionmentioning
confidence: 99%